Internship monitoring and assessment system / Ezza Liyana Jalaludin and Azmi Abu Seman - Jalaludin, Ezza Liyana; Abu Seman, Azmi (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Internship Monitoring and Assessment System is a web-based system that assists students, the internship coordinator, and academic and organisation supervisors during and after the internship programme. Previously, the internship programme at Universiti Teknologi MARA (UiTM) Perlis was not systematic and was based on a manual system. Therefore, by developing this web-based system specifically for monitoring and assessment, students, the internship coordinator, the academic and organisation supervisor could accomplish their job accurately. This study aims to design and develop a web-based system to monitor and assess the internship student’s progress and performance. A waterfall model will be used to develop a complete and successful web-based system. In addition, usability testing is being implemented in this study to evaluate the effectiveness of the Internship Monitoring and Assessment System. There were 30 respondents, including students with Industrial Training experience, the internship coordinator, and the academic and organisational supervisor. According to the test results, most respondents agreed that using this system is simple and comfortable for them. For future work, other researchers can include a Calendar feature to help all users to keep track of daily logbooks, assessment dates and appointment presentation schedules. In conclusion, this system successfully manages and reduces the workload for those involved in the UiTM internship programme.